TECHNOLOGY AND MEDIA IN ARABIC LANGUAGE LEARNING - Syamfa Agny Anggara, Afif Kholisun Nashoih (PRODI PAI FIK UNIRA MALANG, 2025)
The development of information technology has had a significant impact on the world of education, including in learning Arabic. This article aims to review various literature related to the use of technology and media in the Arabic language learning process. This study uses the library research method by analyzing a number of relevant journals, books, and scientific articles. The results of the study show that the integration of technology and modern media is able to increase student motivation, engagement, and learning outcomes in learning Arabic. In addition, the use of technology such as mobile applications, e-learning platforms, interactive multimedia, and social media has been proven to create a more dynamic, contextual, and communicative learning environment. Technology allows for the delivery of more varied materials, such as through learning videos, educational games, and interactive simulations, which indirectly improve the understanding and mastery of Arabic vocabulary and structure. However, the implementation of technology in Arabic language learning also faces a number of challenges, including limited infrastructure, lack of training for teaching staff, and resistance to changes in conventional methods. Therefore, appropriate strategies are needed to effectively integrate technology, such as teacher training, digital-based curriculum development, and the provision of accessible learning resources. This article is expected to provide insight for educators, policy makers, and curriculum developers in utilizing technology as a means to improve the quality of Arabic language learning in the digital era.